Derived data associated with Olsen et al., (2021) Projected Seismic Activity at the Tiger Stripe Fractures on Enceladus, Saturn from an Analog Study of Tidally Modulated Icequakes within the Ross Ice Shelf, Antarctica, JGR: Planets - Olsen, Kira
Derived data used to make Figures 2a-e, 4, 5, and 6 in Olsen et al., 2021 JGR: Planets manuscript, titled Projected Seismic Activity at the Tiger Stripe Fractures on Enceladus, Saturn from an Analog Study of Tidally Modulated Icequakes within the Ross Ice Shelf, Antarctica. Files used to make Figures 2 and 4: DR14_Icequake_Parameters.csv, DR15_Icequake_Parameters.csv, DR14_Icequake_Parameters.csv, DR15_Icequake_Parameters.csv Files used to make figures 5 and 6 (332 files total): Alexandria_*.csv, Baghdad_*.csv, Cairo_*.csv, Damascus_*.csv. Each file contains time series at a single x,y coordinate along a Tiger Stripe Fracture. Column 'y_DFT' gives calculated seismic activity level.